Problems of Zakat Management in Poverty Alleviation in North Sumatra - Septi Sanjaya, Rendy; Khamal Rokan, Mustapa; M. Nawawi, Zuhrinal (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This research aims to see the extent of the problem of zakat in alleviating poverty in North Sumatra. This research method uses a descriptive qualitative method with a quantitative approach. For analysis, use the ANP ( Analytic Network Process ) method with the help of "Super Decision" software. This research uses secondary data originating from the zakat outlook of the BAZNAS Center for Studies and Strategy, accompanied by the opinions of zakat practitioners in North Sumatra. This research was carried out in the North Sumatra Province area and the research was carried out in stages starting from August 2023 to September 2023. The results of the research show that (1) The most priority problem in managing zakat funds in North Sumatra is external problems at 65%, (2) The most priority internal problem is the Amil problem at 70%, (3) The most priority external problem is the Muzakki problem at 49%, (4) The most priority internal solution is the Amil solution at 71%, (5) External solutions the most priority is the Mustahik Solution at 72%, (6) The most priority strategy to be implemented for effective management of zakat funds is Developing the correct mindset for muzakki and mustahik at 61%.